Impacto do sistema de alimentação sobre a qualidade do leite e do queijo de caprinos no semiárido - Medeiros Júnior, Francisco Cesino de (2014)
Dairy products are an important food source, especially from animals fed on pasture whose nutritional, sensory and functional quality is differentiated to human health. Thus, the objective of this research was to evaluate the impact of the feeding system on the quality of milk and cheese from goats in the Brazilian semiarid. Confined and grazing: 24 crossbred goats breed Alpine and divided into two groups of 12 animals according to the food system were used. Trace classes of secondary metabolites was performed by characterizing the presence of these constituents by RMN1H and phytochemical screening of plants to milk and cheese. We evaluated the physicochemical characteristics profile of milk fatty acids and sensory and goats cheese in two feeding systems: grazing and confined. In the species studied, the phytochemical found the presence of various secondary metabolites, highlighting the predominance of flavonoids, steroids and triterpenes evidenced by RMN1H, however, remain only flavonoids present in milk and cheese. Among the physicochemical variables, feeding on pasture influenced the fat content of milk and cheese and thus lipid profile with an increase in unsaturated fatty acids and decreased saturated for milk and cheese from goats fed on pasture , being also observed sensory difference only for aromatic flavor of milk. Diets based on pasture provide improvement in the composition of the fat composition and taste of milk.